2020
DOI: 10.1158/1535-7163.mct-19-0578
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dual BET and PLK1 Inhibitor WNY0824 Exerts Potent Antitumor Effects in CRPC by Inhibiting Transcription Factor Function and Inducing Mitotic Abnormality

Abstract: Castration-resistant prostate cancer (CRPC) is a lethal disease with few treatment alternatives once patients become resistant to second-generation anti-androgens. In CRPC, BET proteins are key regulators of AR-and MYC-mediated transcription, while the PLK1 inhibitor potentially downregulates AR and MYC besides influencing the cell cycle. Therefore, synchronous inhibition of BET and PLK1 would be a promising approach for CRPC therapy. This study developed a dual BET and PLK1 inhibitor WNY0824 with nanomolar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Using the MM/PBSA approach, we estimated the total binding free energies involved in the interaction of WNY0824 with the two macromolecules and our results showed that WNY0824 binds favorably with BRD4‐BD1 and PLK1 with total binding energy values of −42.50 kcal/mol and −51.64 kcal/mol, respectively ( Table 1). Though the observed difference in the estimated Δ G values could translate to dissimilar modes of binding of WNY0824 at the different protein binding sites, the higher value attributed to binding at PLK1 binding site signify considerably higher potency of WNY0824 at the binding site compared to BRD4‐BD1 which is in accordance with experimentally obtained values of IC 50 and Ki values estimated by Xu et al, 2020 [36] . The disparity could also be attributed to the variation in binding site amino acid sequences as well as binding site amino acid conservation.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Using the MM/PBSA approach, we estimated the total binding free energies involved in the interaction of WNY0824 with the two macromolecules and our results showed that WNY0824 binds favorably with BRD4‐BD1 and PLK1 with total binding energy values of −42.50 kcal/mol and −51.64 kcal/mol, respectively ( Table 1). Though the observed difference in the estimated Δ G values could translate to dissimilar modes of binding of WNY0824 at the different protein binding sites, the higher value attributed to binding at PLK1 binding site signify considerably higher potency of WNY0824 at the binding site compared to BRD4‐BD1 which is in accordance with experimentally obtained values of IC 50 and Ki values estimated by Xu et al, 2020 [36] . The disparity could also be attributed to the variation in binding site amino acid sequences as well as binding site amino acid conservation.…”
Section: Resultssupporting
confidence: 89%
“…Also, in a separate investigation probing the dual inhibitory capability of WNY0824 against BRD4 and PLK1, Xu et al . 2020 revealed the nanomolar inhibitory activity of WNY0824 to be 109.30 nM in the BRD4 protein and 22.30 nM in the PLK1 protein [36] . While they posited that these IC 50 values are equipotent in both proteins especially since they recorded excellent anti‐proliferation activity of the compound, we believe the apparent and age‐long shortcomings of using molecular docking studies [60] in isolation necessitates further investigations such as molecular dynamic simulations.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations